Comparative evaluation of properties of a clay based ceramic shaped via four techniques - Torres, Camila Irene (2018)
The results of qualitative and quantitative properties of clay based ceramic are presented in this work. Four different shaping methods and sintering temperatures were used to understand their influence in the final properties of a ceramic material formulated using kaolinite clay and calcined alumina. This material can be used as a structural ceramic for different applications, and there is no pre-established relation between the forming method and the final sintered properties. Forming methods used to prepare the samples were uniaxial pressing (a batch process that allows application in dry samples), extruding (a continuous process that requires moisture), slip casting (a process that allows to shape complex ceramic ware), and lamination (a batch process that requires moisture). Sintering temperatures were in the range of 1100 and 1400 °C. In order to compare how properties behave as the shaping method and sintering temperature change, textural properties, shrinkage, porosimetry, phase composition and mechanical strength were evaluated and analyzed. Scanning electron microscopy and microtomography were employed for analyzing and comparing the developed microstructures. Differences in the resulting properties are explained in terms of the developed crystalline phases and microstructure.